Transport properties and sensing responses of platinum nanoparticles/graphene structure fabricated by thermal annealing process - Mohammad Sarwan Mohd Sanif,; Amgad Ahmed Ali,; Lee, Mai Woon; Lee, Hing Wah; Bien, Daniel Chia Sheng; Abdul Manaf Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The effects of the annealing temperatures and thicknesses on the shapes, sizes and arrangement of platinum (Pt) nanoparticles (NPs) on graphene and their sensing performance for hydrogen (H2) detection were investigated. It shows strong dependency of the annealing temperatures and thicknesses on the properties of NPs. It was found that the proposed technique is able to form the NPs with good size controllability and uniformity even for thick deposited layer, thus eliminating the requirement of very thin layer of below 5 nm for the direct NP synthesis by evaporation or sputtering. The transport properties of Pt NPs/graphene structure and its sensing performance on H2 at room temperature under various H2 concentration were evaluated. The results showed an acceptable sensing response, indicating an innovative approach to fabricate Pt NPs embedded graphene for gas sensing application.